2022
DOI: 10.1021/acs.joc.1c03164
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Z to E Geometrical Isomerization of 1,3-Dienes

Abstract: An efficient cobalt-catalyzed geometrical isomerization of 1,3-dienes is described. In the combination of a CoCl2 precatalyst with an amido-diphosphine-oxazoline ligand, the geometrical isomerization of E/Z mixtures of 1,3-dienes proceed in a stereoconvergent manner, affording (E) isomers in high stereoselectivity. This facile transformation features a broad substrate scope with good functional group tolerance and could be scaled up to the gram scale smoothly with a catalyst loading of 1 mol %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…11 Thus, the development of a stereo-convergent transformation of E / Z mixtures of 1,3-dienes is highly desirable. 12 Recently, a low valence transition-metal was found to be able to serve as a π-Lewis base catalyst for the coupling of dienes with aldehyde and imine electrophiles. 13 For example, Kimura reported a Pd-catalyzed allylation of aldehydes with conjugated dienes with Et 3 B as the Lewis acid activator to obtain dienyl homoallyl alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…11 Thus, the development of a stereo-convergent transformation of E / Z mixtures of 1,3-dienes is highly desirable. 12 Recently, a low valence transition-metal was found to be able to serve as a π-Lewis base catalyst for the coupling of dienes with aldehyde and imine electrophiles. 13 For example, Kimura reported a Pd-catalyzed allylation of aldehydes with conjugated dienes with Et 3 B as the Lewis acid activator to obtain dienyl homoallyl alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above experimental observations and previous reports, 20 the possible catalytic cycles for the cobalt-catalyzed isomerization and reductive C–O bond cleavage reactions are outlined in Scheme 4. First, the ligated cobalt-hydride species ( A ) could be formed in situ by mixing CoCl 2 and ligand with NaBHEt 3 .…”
Section: Introductionmentioning
confidence: 67%
“…Generally, the applications of these catalytic systems were restricted to simple aryl alkyl, diaryl, and dialkyl ketones (Scheme a). However, only limited attention was paid to the catalytic asymmetric hydrosilylation of α-oxygenated ketones, and the enantioselectivity was far from satisfactory in sporadic examples studied. , Very recently, we found that the combination of cobalt salt with a phosphine-amido-oxazoline (PAO) ligand showed unique catalytic activity for alkene and diene isomerization . Following our interest in related fields, in this work we disclose a cobalt-catalyzed asymmetric hydrosilylation of α-acyloxyl and α-phenoxy ketones with a chiral PAO ligand, affording a series of chiral 1,2-diol derivatives with high enantioselectivities (Scheme b).…”
mentioning
confidence: 96%